The immunoglobulin‐like superfamily member IGSF3 is a developmentally regulated protein that controls neuronal morphogenesis. Issue 1 (8th July 2016) - Usardi, Alessia; Iyer, Keerthana; Sigoillot, Séverine M.; Dusonchet, Antoine; Selimi, Fekrije
ABSTRACT: The establishment of a functional brain depends on the fine regulation and coordination of many processes, including neurogenesis, differentiation, dendritogenesis, axonogenesis, and synaptogenesis. Proteins of the immunoglobulin‐like superfamily (IGSF) are major regulators during this sequence of events. Different members of this class of proteins play nonoverlapping functions at specific developmental time‐points, as shown in particular by studies of the cerebellum. We have identified a member of the little studied EWI subfamily of IGSF, the protein IGSF3, as a membrane protein expressed in a neuron specific‐ and time‐dependent manner during brain development. In the cerebellum, it is transiently found in membranes of differentiating granule cells, and is particularly concentrated at axon terminals. There it co‐localizes with other IGSF proteins with well‐known functions in cerebellar development: TAG‐1 and L1. Functional analysis shows that IGSF3 controls the differentiation of granule cells, more precisely axonal growth and branching. Biochemical experiments demonstrate that, in the developing brain, IGSF3 is in a complex with the tetraspanin TSPAN7, a membrane protein mutated in several forms of X‐linked intellectual disabilities. In cerebellar granule cells, TSPAN7 promotes axonal branching and the size of TSPAN7 clusters is increased by downregulation of IGSF3. Thus IGSF3 is a novel regulator of neuronal morphogenesis that might function through interactions with multiple partners including the tetraspanin TSPAN7. This developmentally regulated protein might thus be at the center of a new signaling pathway controlling brain development. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 75–92, 2017